1, 2, 3‐Triazol‐1, 4‐diyl‐Fluoroionophores for Zn2+, Mg2+ and Ca2+ based on Fluorescence Intensity Enhancements in Water. Issue 41 (30th October 2020) - Schwarze, Thomas; Sprenger, Tobias; Riemer, Janine
Abstract: Herein, we represent cation‐responsive fluorescent probes for the divalent cations Zn 2+, Mg 2+ and Ca 2+, which show cation‐induced fluorescence enhancements (FE) in water. The Zn 2+ ‐responsive probes Zn1, Zn2, Zn3 and Zn4 are based on o‐aminoanisole‐ N, N ‐diacetic acid (AADA) derivatives and show in the presence of Zn 2+ FE factors of 11.4, 13.9, 6.1 and 8.2, respectively. Most of all, Zn1 and Zn2 show higher Zn 2+ induced FE than the regioisomeric triazole linked fluorescent probes Zn3 and Zn4, respectively. In this set, ZN2 is the most suitable probe to detect extracellular Zn 2+ levels. For the Mg 2+ ‐responsive fluorescent probes Mg1, Mg2 and Mg3 based on o‐aminophenol‐ N, N, O ‐triacetic acid (APTRA) derivatives, we also found that the regioisomeric linkage influences the fluorescence responds towards Mg 2+ (Mg1 +100 mM Mg 2+ (FEF=13.2) and Mg3 +100 mM Mg 2+ (FEF=2.1)). Mg2 shows the highest Mg 2+ ‐induced FE by a factor of 25.7 and an appropriate K d value of 3 mM to measure intracellular Mg 2+ levels. Further, the Ca 2+ ‐responsive fluorescent probes Ca1 and Ca2 equipped with a 1, 2‐bis(o‐aminophenoxy)ethane‐ N, N, N', N' ‐tetraacetic acid (BAPTA) derivative show high Ca 2+ ‐induced FEs (Ca1 (FEF=22.1) and Ca2 (FEF=23.0)). Herein, only Ca1 ( K d =313 nM) is a suitable Ca 2+ fluorescent indicator to determine intracellular Ca 2+ levels. Abstract : Herein, we synthesized by "click chemistry" cation responsive fluorescent probes to study comparative the sensitivity and selectivity towards Zn 2+, Mg 2+ and Ca 2+ by cation induced fluorescence intensity enhancements in water. These fluorescent probes are suitable tools to measure extracellular Zn 2+ levels or intracellular Ca 2+ level.